Avaliação do Modelo Brams na Formação de Nevoeiro de Radiação com Forte Resfriamento Noturno. Parte ii: Impacto de Diferentes Parâmetros e Parametrizações - Piva, Everson Dal; Anabor, Vagner (Ciência e Natura, 2007)
Experiments are used to evaluate different parameter andparameterization performances to reproduce a radiation fog that is precededby a strong nocturnal cooling rate. The couple Mellor-Yamadaparameterization and the ration of strength of diffusion coefficients betweenscalars and velocity equal one provide the better results. The maximum coolingrate obtained was -5,7oC/11h, being higher than the observed -8,8oC/11h.